Assessment of Nurses’ Knowledge towards Infections of Peripheral Intravenous Cannula in Al-Basrah Teaching Hospital - Aliaa H. Ali; Ahmed T. Saud (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aimed at assessing nurse’s knowledge regarding infection of the peripheral cannula. Descriptive, hospitalbased study was conducted in Al-Basrah city in Al-Basrah Teaching Hospital from October 24th, 2019, to June 11th, 2020. The study included nurses in the hospital; they were (60) nurses. The instrument used for the study was a self-administrated questionnaire; the data were presented in a pre-designed questionnaire firstly. The questionnaire consisted of two parts: socio-demographic characteristics and knowledge about the infection of a peripheral intravenous cannula. Inferential and descriptive statistics have been utilized for the analysis of data. Data were analyzed manually and then through the use of the statistical package for social science (SPSS, v. 23). The results of the study present that the high percent (61.7%) of the study sample are male, (66.7%) of them at the (20-29) year age group, ( 45.0%) of them nursing institute, (61.7% ) their years of work experience were arranged between (1-9 year), most of them (60.0%) don’t have previous training about cannula infection. There has been a significant correlation between nurses’ knowledge, previous training in infection of a peripheral cannula, and level of education, and there has not been any significant correlation between nurses’ knowledge and nurses’ gender, age group, and years of experience. Recommendation: This study recommended establishing a regular training program and workshops about infection control measures, especially for an invasive procedure